Determination of the Optimum Rate of N Fertilizers with Addition of Goat Manure for Production of Cowpea (Vigna unguiculata [L.] Walp) - Liana, Devi; Purnamawati, Heni; Melati, Maya; Wahyu, Yudiwanti (Journal of Tropical Crop Science, 2019)
Cowpea (Vigna unguiculata L. Walp) is one of the potential substitutes of soybean due to its similar nutritional content. This study aims to determine the optimum rate of N fertilizer for the production of cowpea, and to determine the effects of the interaction between N fertilizer rates and goat manure application on cowpea production. The experiment was organized in a split-plot with a complete randomized block design with three replications. The main plot was goat manure, i.e. 0 and 5 tons.ha-1; the sub-plot was nitrogen fertilizer with five rates (0, 50, 100, 150, and 200% of the recommended rate), i.e. 0, 22.5, 45, 67.5, and 90 kg N.ha-1. Application of N fertilizer reduced the 100-seed weight and slightly reduced cowpea yield and yield components. Application of goat manure increased seed dry weight per plant, number of pods per plant, dry pod weight per plant, seed dry weight per m2, productivity, 100-seed weight, and the harvest index. There was no significant interaction between goat manure and different rates of nitrogen in affecting cowpea growth.